Palisaded encapsulated neuroma in tongue - A commonly misdiagnosed peripheral nerve sheath tumor - Agnes Assao; Michele C Pereira; Álvaro H Cury; Cléverson T Soares; Denise T Oliveira (Wolters Kluwer Medknow Publications, 2020)
Palisaded encapsulated (solitary circumscribed) neuromas are benign neural tumors, rarely found in oral mucosa. This case reports a 24-year-old man that presented a unique soft nodule at the left side of the tongue. An excisional biopsy was performed under local anesthesia and histopathological examination of the surgical specimen revealed a well circumscribed mass composed of spindled Schwann cells, often aligned and fasciculated, forming occasional nodules embedded in a fibrous stroma. Histopathological analysis showed the presence of positive cells for S-100, EMA, CD57, and collagen IV. Based on clinical and microscopical features, the diagnosis established was of palisaded encapsulated neuroma. This case report aims to discuss the differential diagnosis among palisaded encapsulated neuroma and the other neural tumors that affect the oral mucosa.